THE EFFECT OF GIVING FERMENTED RICE HULL SUPPLEMENTED WITH Piper betle L. LEAVES IN RATION TO THE PERCENTAGE OF GIBLET MEAT OF FEMALE BALI DUCK - I P. E., Indrawan; Siti, N. W.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2023)
The study aimed to determine the effect of giving fermented rice hull supplemented with Piper betle leaves in rations on the percentage of giblet meat of female bali duck aget 24 weeks. The study used a completely randomized design (CRD) consisting of five treatments were : A (rations without additional rice hull, fermented rice hull and betel leaves), B (rations containing 12.5% rice hull), C (rations containing 12,5% fermented rice hull), D (rations containing 12.5% rice hull and 1% Piper betle leaves) and E (rations containing 12.5% fermented rice hull and 1% Piper betle leaves). Each treatment consisted of four replications and each replication of four female bali ducks aged 24 weeks. The variables observed were percentage of liver, percentage of heart, percentage of bile and percentage of total giblet meat. The results showed that the provision of rations containing 12.5% fermented rice hull and 1% supplemented of Piper betle L. leaves had a significant effect on the percentage of bile but no significant on percentage of liver, percentage of heart, and total percentage of giblet meat. Based on the results of this study, it can be concluded that the giving of fermented rice hull and supplementation of Piper betle L. leaves in ration of female bali ducks reduced the percentage of gizzard but had no effect on the percentage of heart, liver percentage, and the percentage of total giblet meat.   Keywords: fermented rice hull, Piper betle leaves, percentage of giblet meat, female bali duck